DFEM of a post-tensioned precast concrete segmental bridge with unbonded external tendons subjected to prestress changes. (December 2020) - Yuen, Terry Y.P.; Halder, Rudhra; Chen, Wang-Wen; Zhou, Xiangming; Deb, Trissa; Liu, Yang; Tseng, Yang; Wen, Tzu-Han
Abstract: Being cost-effective, rapid construction, high transportability, and maintainability, post-tensioned precast concrete segmental bridges (PT-PCSBs) have been one of the most preferred choices for sites that are restrictive to access. Yet, deterioration due to aging, improper maintenance, and unaccounted shrinkage of bridge decks can cause unexpected prestress loss/gain and alter the structural behaviour of PT-PCSBs, especially with unbonded external tendons. In this regard, this paper presents the development of a rigorous and detailed three-dimensional discrete finite element model (DFEM) for a PT-PCSB, of which both global load-deflection behaviour and local responses were verified against experimental results by Takebayashi et al. (1994) and Jiang et al. (2018). The verified model was then adopted to investigate the effects of prestress loss/gain on the structural responses and failure behaviour. Based on the analysis results, a 20% increase/decrease of prestressing can lead to a 10% increase/16.8% decrease of the moment resistance but a 30.2% decrease/36.6% increase of the deflection capacity. At large prestressing level, e.g. 0.874 f pu, significant crushing of concrete can occur in the bottom region of the bridge at ULS that significantly restricts the joint opening, tendon strain development, and ductility. On the contrary, at the extremely low prestressing level of 0.125 f pu, the bridge decompresses under its self-weight and is very unstable under additional load, resulting in very low ductility and moment resistance. Furthermore, for a regular prestress level of around 0.6 f pu, the stress change in tendons from the effective prestress to the stress in ULS matches the recommendations by ACI318 and AASHTO LRFD but is underestimated by EC2. Yet, the ultimate tendon stress which is less sensitive to the prestress change may be more suitable than the stress change in evaluating the ULS behaviour of PT-PCSBs with unbonded tendons.